Microbiome alterations observed in liver diseases present opportunities for potential fecal transplantation - Heath, Ryan D.; Mir, Fazia; Ibdah, Jamal A.; Tahan, Veysel (Turkish Journal of Gastroenterology, 2016)
Abstract Many disease processes lead to chronic liver disease, however, progress has been made regarding common findings amongst these disease processes that may suggest a path forward for treatment. In particular, common alterations in the intestinal microflora of patients with different etiologies of liver disease may provide a clue as to the pathogenesis of these disorders as well a potential therapy. Data is still scant at this point, however, what is available suggests a promising opportunity for future studies to expand upon what has been demonstrated.